2019
DOI: 10.1111/ap.12385
|View full text |Cite
|
Sign up to set email alerts
|

An Australian adaptation of the Strengthening Families Program: Parent and child mental health outcomes from a pilot study

Abstract: Objective: This is the first pilot study to examine the Australian adaptation of the Strengthening Families Program (SFP), a manualised family intervention recommended internationally in evidence reviews to improve family functioning and child mental health. The study compared two versions (8 vs. 14-session) and longitudinally evaluated outcomes for child emotional and behavioural difficulties, and parental psychological distress. Method: Fifty-eight families from disadvantaged primary schools in regional Vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These included the Family Preservation Services (FPS), Strengthening Family's Program (SFP), Contact Family/Person Program (CFPP), and the Turning into Teens (TINT) program. Except the TINT and SFP programs (Burn et al, 2019), the results of parental and youth reports indicated negative outcomes in a majority of the offered interventions.…”
Section: Intervention With the Familymentioning
confidence: 95%
See 4 more Smart Citations
“…These included the Family Preservation Services (FPS), Strengthening Family's Program (SFP), Contact Family/Person Program (CFPP), and the Turning into Teens (TINT) program. Except the TINT and SFP programs (Burn et al, 2019), the results of parental and youth reports indicated negative outcomes in a majority of the offered interventions.…”
Section: Intervention With the Familymentioning
confidence: 95%
“…SFP showed promising results in reducing pre-adolescent difficulties and parental distress (Burn et al, 2019) but not in addressing adolescent substance misuse (Foxcroft et al, 2017). Despite the worse outcome of reunified children, positive adult-child ties were highlighted by Biehal et al (2015) as a key contributing factor for the overall success of the FPS.…”
Section: Intervention With the Familymentioning
confidence: 98%
See 3 more Smart Citations